Ecotourism of Cireundeu and Basic Sundanese’ Way of Life - Moh Zaenal Abidin Eko Putro; Kustini (Jurnal Manajemen Hutan Tropika, 2022)
Nowadays, some indigenous religion members in Indonesia are still fighting to grasp a fully civil rights recognition granted by the state. However, the way of such effort undertaken by people of Sunda Wiwitan of Cireundeu Cimahi is different. Rather than claiming the civil rights rigorously, they introduce as well as organize community ecotourism by preserving natural environment combined with Sundanese culture. This article aims at uncovering social changing around the shifting point of organizing ecotourism, objections from outsiders and adaptation with social environment whereby they negotiate with. Based on qualitative research which focuses on observation, in-depth interview, as well as literature study, this paper aims to portray the ecotourism initiative and its recent empowerment in this community which currently makes their customary village (kampung adat) well-known as one of the Sundanese cultural tourism destinations for not only Bandung greater area people, but also for the people of outside Bandung and abroad as well. The result shows that albeit some restrictions on expressing civil rights status still occur, having previous experience of losing informal job and objections from other groups alike, this community can maximize their teaching as well as their natural landscape potential in managing self-ecotourism based on their local cultural values.